(untitled) (FIG Joint Land Administration Conference, 2025)
The TED INCRA/UFPR programme addresses long-standing fragmentation in Brazil’s land administration by transforming heterogeneous and siloed datasets into an integrated, standards-based environment. Through participatory and user-centred methods — including design thinking, requirement validation and iterative prototyping — the initiative engaged INCRA professionals and researchers to co-create solutions aligned with operational needs. The resulting infrastructure consolidates tens of thousands of legal, geodetic, environmental and socio-economic records in an institutional repository and a PostgreSQL/PostGIS spatial database, enriched by a standardised data dictionary and conceptual. National (INDE, ET-EDGV) and international (ISO, OGC) standards guided semantic harmonisation and interoperability, while a public monitoring dashboard promotes transparency for managers, oversight bodies and society. The experience reveals not only technical achievements but also cultural and institutional shifts, advancing a data-centric mindset, encouraging collaboration among multiple TED projects, and setting the foundations for the future integration of legacy INCRA systems into coherent spatial data infrastructures.